Evaluation of Groundwater Pollution Nitrogen Fertilizer Using Expert System - Mongkon Ta-oun; Mohamed Daud; Mohd Zohadie Bardaie (agriTECH, 1998)
An expert system was used to correlate the availability of nitrogen fertilizer with the vulnerability of groundwater to pollution in Peninsula Malaysia to identify potential groundwater quality problems. The expert system could predict the groundwater pollution potential under several conditions of agricultural activities and exiting environments. Four categories of groundwater pollution potential were identified base on an N-fertilizer groundwater pollution potential index. A groundwater pollution expert system developed can be use as a tool for the implementation of groundwater pollution potential approach. This facilitated the identification of priority areas for future on site sampling and quantification of groundwater quality. Current cropping patterns and practice need to be evaluated in areas with high susceptibility to groundwater pollution and availability of nitrogen fertilizer. This study indicated that the cultivation of crops requiring high nitrogen fertilizer application rates have the potential to impact groundwater quality. This impact will vary from study area to area on the specific crops grown and their distribution over vulnerable areas.